Arctic National Wildlife Refuge: Background and Issues - Corn, M. Lynne (Library of Congress. Congressional Research Service., 2003)
This report discusses the ongoing debate about whether or not to open the Arctic National Wildlife Refuge (ANWR) for energy development. The report discusses arguments for and against such development and related pieces of legislation. It does not analyze specific proposals to develop or protect the Refuge. Rather, it provides basic material for analyzing possibilities and implications of the major issues that have been the focus of the legislative debate over its fate.